Passing – Captive – Still : (Rare Breed Birds) - Wilson; Snæbjörnsdóttir, Mark; Bryndís (Humanimalia, 2024)
The images in Passing Captive Still depict humans together with birds in cages, their respective presence conjoined at eye-level. In this series, both human actors and the birds themselves are, in every case, seen through the cage bars suggesting a subversive, equalizing narrative. The strategic, pictorial conflation produces an uncanniness, which is both quaint and unsettling. As far as the images themselves are to be believed, both species are apparently “imprisoned” in the pictorial space. In order further to upset what might be the expected power balance of the auction house and event, the various bird individuals, pairs or groupings, appear always in front of the human actors, thereby privileging them within that space. An objective, reflective and contextualising commentary is interspersed alternately with a subjective view, apparently from the position of those held captive against their will.